Scientific Geneology and the Concepts of Sanad in Islamic Boarding School: A Study at Roudhotur Ridwan Islamic Boarding School East Lampung - Muhammad iqbal Alhabsy; Meila Sari; Dedi Setiawan; Irhamudin Irhamudin; Sri Fatmawati (Journal of Research in Islamic Education, 2021)
The connection of the scientific chain from a kyai to a santri is an obligation should be implemented. Kyai from the pesantren has a relationship with each other, both as teacher-student and fellow students of a teacher. Between pesantren there is a relationship, so that the learning concepts applied also have similarities. This is what makes the scientific concept of santri different from the scientific concept of students in non-Islamic boarding schools. This research is a case study at the Roudhotur Ridwan Islamic boarding school, East Lampung. Furthermore, in collecting data, researchers used interview, observation and documentation techniques. The data sources of this research are Kyai and students. The data that has been obtained is then analyzed using interactive data analysis. This study found that the notion of sanad in Islamic boarding schools is a tradition to maintain the integrity and purity of knowledge.